Portraits of Labor Market Exclusion 2.0 - World Bank Group; European Commission (World Bank, Washington, DC, 2018)
This report is part of a joint study between the European Commission (EC), the World Bank, andthe Organisation for Economic Co-operation and Development (OECD). It aims to inform activation and employment support and social inclusion policy making and programs through an improved understanding of labor market barriers. The people within and across countries characterized as labor market vulnerable are not all the same. Different life situations lead people to being unemployed, inactive, or precariously employed. Various personal constraints may induce people to take temporary or precarious employment, work a reduced number of hours, or earn very low incomes despite being engaged in full-time work. All of these are considered the labor market vulnerable, and a better understanding of their differences and similarities is essential to successful labor market inclusion. Governments need to know who the labor market vulnerable are and what barriers keep them out of work or in unstable employment. This information will help countries meet the inclusive growth priorities of the Europe 2020 Strategy (EC 2010) and the European Pillar of Social Rights; it also aligns with recognizing the potential negative impacts of labor market vulnerability on long-term growth.